Effect of changes in Interest Rates on Household Consumption - Ahmad, Srifatmawati; Azizi, Muhammad (PT. Anagata Sembagi Education, 2025)
This study aims to analyze the effect of changes in interest rates on household consumption in Indonesia by employing a quantitative method with a causal associative approach. The analysis uses secondary time-series data from 2014 to 2024, obtained from official institutions such as Bank Indonesia and the Central Statistics Agency (BPS). The variables examined include interest rates, household income, and inflation as independent variables, while household consumption serves as the dependent variable. Data analysis was conducted using multiple linear regression through SPSS. The results indicate that interest rates have a negative and significant effect on household consumption, implying that higher interest rates discourage spending by increasing borrowing costs. On the other hand, household income positively and significantly affects consumption, suggesting that increased income boosts purchasing power. Inflation is also found to negatively influence consumption, reflecting reduced purchasing capability during periods of rising prices. The model’s goodness of fit, as measured by R Square, shows that 81.4% of the variation in household consumption can be explained by the three independent variables. These findings emphasize the importance of interest rate and inflation control in maintaining household consumption stability and overall economic health.